2018
DOI: 10.1186/s40644-018-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

68 Ga-PSMA-PET/CT for the evaluation of pulmonary metastases and opacities in patients with prostate cancer

Abstract: BackgroundThe purpose of this study was to investigate the imaging properties of pulmonary metastases and benign opacities in 68Ga-PSMA positron emission tomography (PET) in patients with prostate cancer (PC).Methods68Ga-PSMA-PET/CT scans of 739 PC patients available in our database were evaluated retrospectively for lung metastases and non-solid focal pulmonary opacities. Maximum standardized uptake values (SUVmax) were assessed by two- and three-dimensional regions of interest (2D/3D ROI). Additionally CT fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Particularly, lung nodules appear to lead not only to interreader but also intercriteria disagreement (equivocal vs. negative) in the PET/CT group. Although lung metastases from PC are relatively rare (16,17), small lung nodules can often be problematic in interpretation. Compared with PSMA-RADS, EANM and PROMISE criteria have a greater emphasis on the existence of PSMA uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, lung nodules appear to lead not only to interreader but also intercriteria disagreement (equivocal vs. negative) in the PET/CT group. Although lung metastases from PC are relatively rare (16,17), small lung nodules can often be problematic in interpretation. Compared with PSMA-RADS, EANM and PROMISE criteria have a greater emphasis on the existence of PSMA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…That is, EANM and PROMISE criteria generally regard lesions without elevated PSMA uptake as negative findings (9,10), whereas PSMA-RADS can include such lesions in the equivocal criteria (PSMA-RADS-3D) (11). When applying these criteria, one should keep in mind that small lesions such as lung nodules can be falsely judged as negative because of the partial-volume effect (17). However, this problem can be solved by clearly stating information on PSMAnegative lesions in the interpretation report, regardless of the criteria used.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical research has suggested that despite an overall increase in PSMA expression during progression of PCa from androgen sensitivity to androgen independence, some metastatic cell lines lose PSMA expression [ 75 ]. A significant proportion of liver metastases may also lack PSMA expression, although most liver metastases highly overexpress PSMA [ 76 ]. Heterogeneity of PSMA expression may partly explain why about 30% of patients do not respond to 177 Lu-PSMA RLT [ 77 ].…”
Section: Psma Radioligand Therapy (Rlt)mentioning
confidence: 99%
“…In our case, pulmonary tuberculosis shows mild 68 Ga-PSMA uptake, which is similar to the most lung benign diseases with mild to moderate PSMA expression. In addition, most PSMA-positive lung malignant diseases demonstrate intense PSMA uptake, and the SUVmax is relatively higher than benign diseases [3,4]. Thus, the SUVmax may be of differential significance for most PSMA-positive lung lesions.…”
Section: Discussionmentioning
confidence: 99%